Synthesis of CdSe/ZnS and CdTe/ZnS quantum dots: refined digestive ripening - Cingarapu, Sreeram; Yang, Zhiqiang; Sorensen, Christopher M.; Klabunde, Kenneth J. (My University, 2012)
We report synthesis of CdSe and CdTe quantum dots (QDs) from the bulk CdSe and CdTe material by evaporation/co-condensation using the solvated metal atom dispersion (SMAD) technique and refined digestive ripening. The outcomes of this new process are (1) the reduction of digestive ripening time by employing ligands (trioctylphosphine oxide (TOPO) and oleylamine (OA)) as capping agent as well as digestive ripening solvent, (2) ability to tune the photoluminescence (PL) from 410 nm to 670 nm, (3) demonstrate the ability of SMAD synthesis technique for other semiconductors (CdTe), (4) direct comparison of CdSe QDs growth with CdTe QDs growth based on digestive ripening times, and (5) enhanced PL quantum yield (QY) of CdSe QDs and CdTe QDs upon covering with a ZnS shell. Further, the merit of this synthesis is the use of bulk CdSe and CdTe as the starting materials, which avoids usage of toxic organometallic compounds, eliminates the hot injection procedure, and size selective precipitation processes. It also allows the possibility of scale up. These QDs were characterized by UV-vis, photoluminescence (PL), transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and powder XRD.
Keywords: Synthesis; Quantum dots; SMAD technique; Refined digestive ripening